Charge Distributions in Nucleons Able to Create the Nuclear Structure - Kaliambos, L. A. (HNPS Advances in Nuclear Physics, 2020)
Considerable charge distributions in nucléons as multiples of the fractional charges 2e/3 and -e/3 are determined after a careful analysis of the magnetic moments and the results of the deep inelastic scattering. In fact nucleons have fairly large magnetic moments which imply charge distributions of 8e/3 and -8e/3 along the peripheries of proton and neutron respectively. According to the deep inelastic scattering the corresponding charges of -5e/3 and 8e/3 are limited at the centers of the above nucleons. Basic equations derived from such distributed charges lead to the orientation of spins of nucleons and give strong and short ranged forces like the dipole-dipole interactions leading also to the well known binding energy of the deuteron which operates in radial direction with S=1. This operation due to the basic electromagnetic interaction of the opposite charges along the peripheries is in contrast to the Pauli principle. According to these fundamental interactions, p-p and n-n systems repel and only the p-n bonds form rectangles and closely packed parallelepipeds for the structure of nuclei providing an excellent description of nuclear properties.